2015
DOI: 10.1016/j.ajpath.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

YAP1 Is a Driver of Myofibroblast Differentiation in Normal and Diseased Fibroblasts

Abstract: Dupuytren disease is a fibrotic disorder characterized by contraction of myofibroblast-rich cords and nodules in the hands. The Hippo member Yes-associated protein 1 (YAP1) is activated by tissue stiffness and the profibrotic transforming growth factor-β1, but its role in cell fibrogenesis is yet unclear. We hypothesized that YAP1 regulates the differentiation of dermal fibroblasts into highly contractile myofibroblasts and that YAP1 governs the maintenance of a myofibroblast phenotype in primary Dupuytren cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 41 publications
5
100
0
Order By: Relevance
“…Interestingly, the effects of YAP silencing were not as profound as those of verteporfin, suggesting that verteporfin may also mediate its effects through other non-YAP-dependent mechanisms. Indeed, although prior studies have mostly focused on the profibrotic activity of YAP, 36,37 it is possible, for example, that verteporfin-induced reductions in TAZ may also have important effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the effects of YAP silencing were not as profound as those of verteporfin, suggesting that verteporfin may also mediate its effects through other non-YAP-dependent mechanisms. Indeed, although prior studies have mostly focused on the profibrotic activity of YAP, 36,37 it is possible, for example, that verteporfin-induced reductions in TAZ may also have important effects.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is consistent with prior evidence of physical interactions between YAP/TAZ and Smad2/3 in the nucleus, [14][15][16] and it is in line with reports from our group and others indicating that YAP and TAZ exhibit profibrotic activity. [35][36][37] Indeed, Speight et al 24 previously showed a role for TAZ in controlling a-SMA expression in injured epithelium as part of epithelial-myofibroblast transition. 35 Similarly, recent reports have showed that a stiff environment promotes YAP/TAZdependent activation of fibroblasts and hepatic stellate cells, promoting matrix synthesis independent of TGF-b, possibly through the induction of CTGF and PAI1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown that TGF-β-induced myofibroblastic (i.e., CAF) activation is dependent on Rho activity and nuclear translocation of Yes-associated protein-1 (YAP1). This TGF-β-mediated process is known to transcriptionally regulate proteins involved in proliferation and apoptosis which ultimately culminates in altered ECM production [121]. In fact, YAP has been shown to play a role in both ECM remodeling and in cellular responses to altered ECMs.…”
Section: Desmoplastic Sdr: Cancer-associated Fibroblasts-ecm Interactmentioning
confidence: 99%
“…Novel players have been implicated in the pathogenesis of DD such as Wilm’s tumour protein-1 (WT1) [31•] and YAP [32•]. YAP1, a member of the Hippo pathway, which has recently been shown to promote differentiation of fibroblasts into myofibroblasts, potentially acts downstream of TGFβ [32•].…”
Section: Molecular and Cellular Alterations In Dd Degenerationmentioning
confidence: 99%
“…YAP1, a member of the Hippo pathway, which has recently been shown to promote differentiation of fibroblasts into myofibroblasts, potentially acts downstream of TGFβ [32•].…”
Section: Molecular and Cellular Alterations In Dd Degenerationmentioning
confidence: 99%